Penciptaan Convertible pada Busana Ready to Wear Deluxe dengan Sumber Ide Rumah Adat Tikel Balung - Dinda Marthania Putri Mulyono; Deny Arifiana; Mein Kharnolis; Ma’rifatun Nashikhah (Practice of Fashion and Textile Education Journal, 2025)
This research is a research on the creation of artwork that describes convertibles on ready-to-wear deluxe fashion with the source of the idea of ​​the Tikel Balung traditional house. The purpose of this creation research is (1) To describe the formulation of ideas and concepts for creating convertibles on ready-to-wear deluxe fashion with the source of the idea of ​​the Tikel Balung traditional house, (2) To describe the process of creating convertibles on ready-to-wear deluxe fashion with the source of the idea of ​​the Tikel Balung traditional house, (3) To describe the finished results of convertibles on ready-to-wear deluxe fashion with the source of the idea of ​​the Tikel Balung traditional house, and (4) To describe the presentation of convertibles on ready-to-wear deluxe fashion with the source of the idea of ​​the Tikel Balung traditional house. The method used in this research is the method of creation of works, namely through 4 stages of research starting from exploration, design of works, manifestation of works, to presentation of works. The creation of fashion works resulted in 1 men's clothing and 2 women's clothing with the application of convertibles on the three clothes. One men's clothing design with a convertible construction size on the pants and two women's clothing designs with modular convertibles applied to the outer and pants. Manipulating fabric in the creation of this deluxe ready to wear clothing is taken from the slimpet motif which is the main motif of the Tikel Balung traditional house, which is applied using printing, embroidery techniques, and a combination of the two.